Water Resource Planning in Latin America and the Caribbean - Isabel Guzmán-Arias; Julio César Calvo-Alvarado (Tecnología en Marcha, 2016)
The current state of water resource management and planning in Latin American and Caribbean countries is described and discussed. The analysis is based on the most recent studies on this subject, which provide elements such as updated and duly verified information on the legislative, institutional and organizational reality in the countries of the region. Integrated planning and management of water resources has been characterized by a great diversity of legal and institutional approaches, including long debates on water bills and constant proposals to amend the few water laws in force (Dourojeanni & Jouravlev, 2002.) Some countries such as Mexico and Chile have been more successful in achieving important goals. However, Continuity in time and appropriate coverage are still required, as they are both lacking for now.